Vertical capacity of bucket foundations in undrained soil - Barari, Amin; Ibsen, Lars Bo (Journal of Civil Engineering and Management, 2014)
Offshore wind turbine structures are traditionally founded on gravity concrete foundations or mono-piles. Bucket foundations were developed for the offshore oil and gas industry and are now being used in wind turbine construction. The loading in this application is characterized by a vertical load due to the slender construction combined with horizontal forces inducing a large overturning moment. Field tests on bucket foundations were performed to gain insight into the vertical load response of bucket foundations in clay soils. The field tests were accompanied by finite element numerical simulations in order to provide a better understanding of the parameters influencing bucket foundation behaviour.